Pemberdayaan Perempuan Pesisir dalam Pemanfaatan Pangan Lokal untuk Pencegahan Stunting melalui Pendampingan Kesehatan - Wahab, Masyitah; Muin, Rahmatullah; Ariani, Ariani; Sulaiman, Yulianah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Stunting remains a major public health issue in Indonesia, particularly in coastal areas where access to health services and nutrition information is limited. Fishermen’s wives play a vital role in sustaining household economies and ensuring family nutrition. Objective: This program aims to empower fishermen’s wives through the development of Sambusa Mandar, a traditional local food enriched with protein and micronutrients from local resources combined with health education and entrepreneurial capacity building to prevent stunting and improve family welfare. Method: The program was carried out in four stages: coordination, needs assessment, and development of Standard Operating Procedures (SOP) for hygienic sambusa processing;  design and implementation of digital-based promotion through social media and website platforms; training and dissemination, including the use of a sambusa skin-making machine, food safety practices, and business management; and promotion, public dissemination, and program evaluation involving local stakeholders. Result: The program significantly improved beneficiaries’ knowledge of nutrition and food hygiene, increased production capacity from 300 to 600–1000 sambusa skins per day, and standardized product quality through SOP-based processing. Moreover, the adoption of digital marketing expanded product reach and visibility, while health education raised awareness of balanced diets to prevent stunting. The program also enhanced household income and opened new entrepreneurial opportunities for coastal women, aligning with the Sustainable Development Goals (SDGs) 2 (Zero Hunger), 3 (Good Health and Well-being), and 8 (Decent Work and Economic Growth). Conclusion: Empowering fishermen’s wives through nutritious food processing and health education has improved family nutrition, reduced the risk of stunting, and created new economic opportunities. The integration of local food innovation, SOPs, and digital promotion ensures sustainability and supports coastal community welfare.